Ecology and Carbon sequestration of secondary forests at Sabal, Sarawak - Karyati, - (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Global climate change in the recent decade is caused by disturbance of energy balance between the earth and atmosphere due to an increase of green house gasses (GHG), particularly carbon dioxide (CO2). The land use change is one of many human activities that may affect to increase CO2. The conversion of primary forests to shifting cultivation may lead to an increase of fallow lands. Succession process of fallow lands will develop secondary forests. Tropical secondary forests have an important contribution in the global, regional, national, and local scales. These forests have valuable role in relationship to climate change, is a source and sink of carbon (C). A study on ecology and carbon sequestration of different stage secondary forests was conducted in Sabal, Sarawak. This study reviews and gives holistic information on the ecological and C sequestration of various stage secondary forests. The ecological study focused on analysis of vegetation and soil properties. The analysis of vegetation includes floristic structure, composition and diversity at different ages of secondary forests as well as diameter at breast height (DBH) increment of selected tree species. The early secondary succession process showed rapid dynamic change on floristic structure and composition. In terms of density, summed dominance ratio (SDR), and importance value index (IVi), the most dominant species were dominated by pioneer species in Temuda I, Temuda II, and Belukar I. The dominance of pioneer species appeared in the early succession stage, and decreased gradually in Belukar I and Belukar II. The occurrence of late pioneer species and secondary species were dominated in these two Belukar. In Belukar II, the dominance of pioneer species were not exists. The result of analysis for vegetation was used to select sample trees in developing allometric equation. The specific allometric equations of different age secondary forests were developed to estimate above ground biomass (AGB) accurately, for both seedlings and saplings (DBH of < 5 cm) and trees (DBH of > 5 cm). Based on the best allometric equations, the AGB of different age secondary forests were estimated. The C stock and C sequestration were described from this estimation. Soil morphological and physicochemical properties differed at various stages of fallow periods. The above ground C stock shows strong relationship to fallow period, but no relationship is shown between below ground C stock and abandoned period. The result showed that there were positive and negative correlations between soil properties and vegetation parameters. The trends and changes of floristic structure and composition were influenced by dominant species. Several species of secondary forests, such as Cratoxylum arborescens, C. glaucum, Endospermum diadenum, Euodia glabra, Macaranga gigantea, M. triloba, Vernonia arborea, and Vitex pubescens were selected to assess their DBH increment. The results showed that DBH increments vary among species, DBH classes, measurement assessment, and measurement periods. There is a weak relationship and correlation between DBH increment of selected tree species and climate elements. Floristic structure, composition, and diversity were responsible for influence of differences in AGB, C stock, and C sequestration at different age secondary forests. The study reveals that vegetation and soil properties of secondary forests varied and developed under different stages of fallow periods. In respect to the role and ability of secondary forests to develop dynamically, particularly at the early stage secondary succession process, their existence needs more attention because secondary forests may sequestrate a great amount of C as well as their floristic structure, composition, and diversity. In the future, the secondary forests are expected to be able to reach the maturity although it might be never the same as the primary forests.